Underlying data for the paper Techno-economic analysis of supercritical carbon dioxide cycle integrated with coal-fired power plant"" - Thanganadar, Dhinesh; Asfand, Faisal; Patchigolla, Kumar; Turner, Peter J. (Cranfield University, 2021)
Underlying data for the journal paper "Techno-economic analysis of supercritical carbon dioxide cycle integrated with coal-fired power plant"
Keywords: 'Supercritical CO2 cycle'; 'techno-economic feasibility'; 'optimisation'; 'Coal-fired power power plant'; 'power cycle'; 'Power and Energy Systems Engineering (excl. Renewable Power)'; 'Energy Generation; Conversion and Storage Engineering'